Fiscal Sustainability in Remittance-Dependent Economies - Chami, Ralph (IMF Working Papers; Working Paper ;, 2009)
We investigate the impact of remittances on public debt sustainability and detail how the traditional debt-to-GDP ratio can be modified to create a more accurate representation of debt sustainability for a country that receives significant remittance inflows. The main result is that inclusion of remittances into the traditional debt sustainability analysis alters the amount of fiscal adjustment required to place debt on a sustainable path. While preliminary, these results are indicative of how a one-size-fits-all stability analysis may be inappropriate when evaluating the stance of fiscal policy for countries with different balance of payments characteristics.